Mixing Time Scale Determination in Microchannels Using Reaction Calorimetry. Issue 5 (7th January 2019) - Reichmann, Felix; Vennemann, Kai; Frede, Timothy Aljoscha; Kockmann, Norbert
Abstract: Mixing time scales are derived from heat flux profiles for an instantaneous and exothermic reaction in a commercially available microreactor. A continuous reaction calorimeter, based on numerous heat flux sensors, is used to record spatially resolved heat flux profiles in steady state. Total volumetric flow rate is varied at constant flow rate ratio and the region of main reaction progress is shifted within the microreactor according to the advancement of the mixing process. Secondary flow patterns, induced by Dean mixing elements within the microchannel at higher flow rates, enhance the mixing. Results display a decrease in mixing time at increased flow rates and energy dissipation rate. Additionally, the passive micromixer is evaluated regarding its efficiency. Abstract : Mixing time has a crucial influence on chemical transformation and reactor performance. In this work, mixing time scales are derived from heat flux profiles of an instantaneous and exothermic reaction recorded with a continuous reaction calorimeter.